COVID-19 vaccination reduces mortality in patients on maintenance hemodialysis - Tylicki, Leszek; Biedunkiewicz, Bogdan; Puchalska-Reglińska, Ewelina; Gellert, Ryszard; Burnier, Michel; Wolf, Jacek; Dȩbska-Ślizień, Alicja (Frontiers in Medicine, 2022)
Patients on maintenance hemodialysis (HD) have a very high risk of death in the course of COVID-19. The aim of the study was to assess the effectiveness of COVID-19 vaccination to reduce the incidence of COVID-19 and the fatality rate in HD patients. A retrospective registry-based cohort study was performed in all HD adult patients in the Pomeranian Voivodeship. Vaccinations were carried out from January to April 2021 with mRNA vaccines, either BNT162b2 or mRNA-1273 with two-dose schedule. In the first analysis (2nd pandemic wave), 1160 unvaccinated patients were included (59.7% males, 25.7% diabetic). In the second analysis (4th pandemic wave), 1131 (59.4% male, 30.7% diabetic) individuals were included, 1042 (92.13%) were fully vaccinated. 315 HD patients (27.2%) were COVID-19 positive during the 2nd wave, and 6.9% (78/1131) during the 4th wave. Within the fully vaccinated patients of the 4th wave, 60 were COVID-19 positive, 5.8% vs 20.2% of unvaccinated COVID-19 positive patients in 2nd wave, respectively. COVID-19 incidence rate ratio (IRR) was 0.21 (4th wave-vaccinated vs. 2nd wave-unvaccinated) indicating a 79% reduction. The IRR between vaccinated and unvaccinated patients of the 4th wave was 0.28 in favor of vaccinated patients with 72% reduction. In 2nd wave, 93 patients deceased as a result of COVID-19 (fatality rate: 29.5%). The fatality rate of fully vaccinated patients during the 4th wave was 6.7% (p=0.004). Fatality rate in the 4th wave within unvaccinated patients accounted for 11.1%. Conclusion: Significant clinical effectiveness of COVID-19 vaccination was demonstrated in a multicenter study in HD patients.